The Chemistry of the English Environment: An Ethnographic Study of Language Practices in an Islamic Boarding School - Ahmad Subhan Roza; Trisna Dinillah Harya; Widhiya Ninsiana (CV. Creative Tugu Pena, 2026)
This study investigated the development of an English language environment in an Islamic boarding school context where learners often had limited opportunities to use English beyond the classroom. Previous studies tended to examine language learning factors separately, leaving a gap in understanding how environmental elements functioned as an integrated system. To address this gap, this research proposed the concept of the “chemistry” of the English environment, referring to the dynamic interaction between institutional policy, teaching practices, and social communication. The study employed a qualitative ethnographic design conducted at the Modern Islamic Boarding School Darussalam Gontor, involving school leaders, teachers, and students as participants. Data were collected through observation, interviews, questionnaires, and document analysis, and analysed using an interactive model of data reduction, display, and verification. The findings revealed that the English environment was successfully constructed through the integration of formal instruction and informal daily interaction supported by strict discipline and continuous exposure. It was also found that institutional control played a significant role in shaping language habits, although a gap remained between external motivation and consistent language use. Furthermore, peer interaction and student organisations contributed to sustaining communicative practices in natural settings. These findings suggested that a structured and immersive environment could effectively support second language acquisition when supported by consistent policy and social engagement. This study contributed to the field by offering an integrated model of language environment development and provided practical implications for designing sustainable English learning ecosystems in similar educational context.